Management of HIV/AIDS Services in MSM Group (Men Who Have Sex With Men) - Triyono, Wahyu Wirawan; Menap, Menap; Sismulyanto, Sismulyanto; Saimi, Saimi; Sulaiman, Lalu (Jurnal Kesehatan Prima, 2024)
The focus of the global problem that is of concern both in the world and in Indonesia is the HIV/AIDS case, that reported HIV/AIDS cases in districts/cities in Indonesia were 22,331 HIV cases and 4,534 AIDS cases. Meanwhile in NTB in 2022, there were 1471 accumulated AIDS cases and the addition of 192 new cases, in Central Lombok Regency there were 378 HIV cases and 220 AIDS cases as of September 2022, as well as 211 HIV cases in the MSM group. The strategy determined was to carry out in-depth interviews using the Snow Ball method with 4 informants, namely the VCT/KTH Mandalika Team at Praya Regional Hospital, Management at Praya Regional Hospital, MSM Clients at KTH at Praya Regional Hospital and the HIV Program Holder of the Central Lombok District Health Service. Test the validity of the data with Credibility, Continuous Observation, Triangulation, Transferability, Depreciability, Confirmability. This research has received ethical approval from the Ethics Committee of Qamarul Huda Badaruddin Bagu University with Number: 022/EC/FKES-UNIQHBA/YPPQH/VIII/2023. Management of HIV/AIDS Prevention Services in the MSM Group at KTH Mandalika RSUD Praya still needs to improve the effectiveness of HIV/AIDS prevention, more intensive strategic planning is needed to overcome the increase in HIV prevalence, involving an approach through a TEAM of Field Officers in providing more effective education and social support through VCT services and hotline counseling. Coordination and a stable organizational structure in KTH Mandalika RSUD Praya cannot be ignored, so that response efforts can run more focused. Staff training and development, especially those related to handling PLWHA, needs to be based on objective selection and unit needs, while the use of information technology, such as the SIHA 2.1 application and RS SIM, can be improved to ensure accurate recording and reporting. Management of BHP and ARV availability needs to be optimized through efficient coordination with the District and Provincial Health Services, and regular evaluations need to be carried out to increase distribution efficiency. Implementing the recommendations from 4 informants can have a significant positive impact in managing the management of HIV/AIDS prevention services at KTH Mandalika RSUD Praya, so as to reduce HIV transmission, and provide better support to PLWHA in the MSM community..